Pengaruh Model Pembelajaran Problem Posing Terhadap Prestasi Belajar Siswa MTs Al-Raisiyah Sekarbela - Dian Purwitarini (Unversitas Muhammadiyah Mataram, 2019)
Abstract: This study aims to find out the influence of Problem Posing learning model on math learning achievement in class VII MTS Al-Raisiyah comparison material. The type of research used was